Data management technologies and applications : 4th International Conference, DATA 2015, Colmar, France, July 20-22, 2015 revised selected papers /: 4th International Conference, DATA 2015, Colmar, France, July 20-22, 2015 revised selected papers. (2016) - Unknown
No abstract available